Analysis of the Influence of the Use of Web-Based Academic Information Systems on the Effectiveness of Student Academic Services - Taufiq Muhammad Tri'Adi; Rafa Dzikry Hendrawan (STEBIS Bina Mandiri, 2026)
The abstract is written using Times New Roman font size 10 pt, single-spaced, and margins according to the Pamulang University journal provisions (top 3 cm, left 4 cm, right 3 cm, bottom 3 cm). The abstract contains the research objectives, methods, results, and conclusions concisely in one paragraph. The development of information technology in the field of computer science has encouraged universities to adopt web-based academic information systems to improve the quality of academic services. This study aims to analyze the effect of the use of a web-based Academic Information System (SIAKAD) on the effectiveness of student academic services. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires distributed to students of the Information Systems Study Program. Data analysis techniques used validity tests, reliability tests, and simple linear regression analysis. The results of the study indicate that the use of web-based SIAKAD has a significant effect on the effectiveness of student academic services. Thus, the implementation of a web-based information system is proven to be able to increase the efficiency, accuracy, and satisfaction of academic services.